Spatial Differentials in Fertility and the 0-6 Year Sex Ratio in India, by District: 2001 - Amber Shevaun McIlwain (2007)
Most countries have a fairly stable sex ratio, however, in societies where there is a marked preference for male children a different pattern is seen, one where population sex ratios are male dominant. This is the case for India, a country with an historical and cultural basis for son preference. Findings from India's 2001 census confirm that excessfemale mortality persists in much of India, even as the country experiences rapid declines in fertility levels. The objective of this study is twofold: (1) to understand the spatial differentials in total fertility rates and the 0-6 year child sex ratio in India and (2) to investigate the relationship between these two demographic indicators. Cultural, socioeconomic, demographic, and geographic determinants of fertility and the sex ratio were examined in a multivariate framework using district-level data from the 2001 census. Findings conclude that region matters when explaining the spatial variation in fertility and the sex ratio but that no correlation exists between them. Female literacy had the greatest impact on fertility decline, whereas the sex ratio was affected by cultural factors